2023
DOI: 10.3390/ijms24087003
|View full text |Cite
|
Sign up to set email alerts
|

A Culturomics-Based Bacterial Synthetic Community for Improving Resilience towards Arsenic and Heavy Metals in the Nutraceutical Plant Mesembryanthemum crystallinum

Abstract: Plant-growth-promoting bacteria (PGPB) help plants thrive in polluted environments and increase crops yield using fewer inputs. Therefore, the design of tailored biofertilizers is of the utmost importance. The purpose of this work was to test two different bacterial synthetic communities (SynComs) from the microbiome of Mesembryanthemum crystallinum, a moderate halophyte with cosmetic, pharmaceutical, and nutraceutical applications. The SynComs were composed of specific metal-resistant plant-growth-promoting r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…In a previous study, it was shown that inoculation with these consortia increased the concentration of malate and citrate in the presence of heavy metal stress [59]. Other studies also show that inoculation with endophytes modulates the metabolome of this plant [33,60]. On the other hand, the specific modulation of the secondary metabolism, precisely of compounds with pharmaceutical interest, was observed.…”
Section: Discussionmentioning
confidence: 88%
“…In a previous study, it was shown that inoculation with these consortia increased the concentration of malate and citrate in the presence of heavy metal stress [59]. Other studies also show that inoculation with endophytes modulates the metabolome of this plant [33,60]. On the other hand, the specific modulation of the secondary metabolism, precisely of compounds with pharmaceutical interest, was observed.…”
Section: Discussionmentioning
confidence: 88%
“…Although the most convenient method could have been the individual treatment by strain, we considered that a small consortium in the synthetic community made more sense to cover most of the required skills, which no single strain seemed capable of covering. This approach has provided more promising results in complex systems, such as our object of study, as we can find in the studies by Schmitz et al, Yin et al, and Flores-Duarte et al [ 78 , 103 , 104 ]. Apart from the improvements described before in the germination and development of the B. bituminosa seedlings, this treatment showed that it was able to improve the degree of aggregation, something that we verified both through the Slaking index, as well as by granulometry ( Figure 6 and Figure 7 ).…”
Section: Discussionmentioning
confidence: 91%
“…PGPB also have the capacity to solubilize phosphate and increase its availability for absorption and use by plants. By utilizing culturomics, Flores-Duarte et al [ 210 ] identified 13 features in PGPB, including biofilm development and phosphate solubilization, in their study.…”
Section: Methods Of Microbiome Studiesmentioning
confidence: 99%